Simplifying
25x + -15 = 2y
Reorder the terms:
-15 + 25x = 2y
Solving
-15 + 25x = 2y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '15' to each side of the equation.
-15 + 15 + 25x = 15 + 2y
Combine like terms: -15 + 15 = 0
0 + 25x = 15 + 2y
25x = 15 + 2y
Divide each side by '25'.
x = 0.6 + 0.08y
Simplifying
x = 0.6 + 0.08y
Answer:
(6, -3)
Step-by-step explanation:
Answer:
about 90% of the time?
Step-by-step explanation:
X= 18
So that you can help yourself better use Math-way!!
Answer: (13,-7)
Step-by-step explanation:
By using the formula ![(x_{m},y_{m}) =(\frac{x_{1}+x_{2} }{2},\frac{y_{1}+y_{2} }{2} )](https://tex.z-dn.net/?f=%28x_%7Bm%7D%2Cy_%7Bm%7D%29%20%20%3D%28%5Cfrac%7Bx_%7B1%7D%2Bx_%7B2%7D%20%20%7D%7B2%7D%2C%5Cfrac%7By_%7B1%7D%2By_%7B2%7D%20%20%7D%7B2%7D%20%29)
is the coordinates of the midpoint.
For finding the midpoint X variable do:
![(\frac{4+22}{2})=13](https://tex.z-dn.net/?f=%28%5Cfrac%7B4%2B22%7D%7B2%7D%29%3D13)
For finding the midpoint Y variable do:
(you can either keep the parenthesis or take them out. Either way, the answer is the same.
Considering coordinate numbers follow the format: (x,y), you'll simply just substitute the numbers found above into their respective places.
x: 13
y: -7
(13,-7).